(untitled) (Academic Journal of Internal Affairs, 2020)
In connection with the coronavirus pandemic the government implemented a special legal order and emergency on 11 th March 2020. For the containment of coronavirus was set up an Operational Group to supply the population with authentic and up to date information on measurements helping prevention, round of duties, measurements of authorities. They inform the wide public, the whole society day by day. What kind of challenges brings the pandemic situation for a competent expert of law enforcement and what can he advise for staff members? Among others were these questions asked from Dr. Albert Torma, Chief Medical Officer of Law Enforcement. After termination of the emergency we will ask him again to inform us about his experiences and results on treatment of the emergency.